Effectiveness of platelet rich plasma injection for achilles tendon injury in wistar rats: An experimental study - Nasution, Nino; Reza, Muhammad (Jurnal Prima Medika Sains, 2025)
Tendon injuries, particularly Achilles tendon ruptures, significantly impact athletes and labourers, affecting daily activities and quality of life. The platelet plasma rich (PRP) injections have emerged as a treatment option due to their abilities in stimulating growth factors, essential for the healing processes. This study investigates the effectiveness of PRP injections in healing Achilles tendon injuries in Wistar rats. Thirty male Wistar rats were divided into three groups: Group 1 received a 100 µL PRP injection, Group 2 received a 50 µL PRP injection, and Group 3 received a 100 µL NaCl injection as a control. The Achilles tendons were surgically transacted and sutured using modified Kessler method, followed by PRP or NaCl injections. Rats were euthanized on days 15 and 30 for histological and biomechanical evaluations. This study found that PRP administration had a significant effect on histological tendon healing on the 15th and 30th, with the best improvement at a PRP dose of 100 µL, especially in the early phase of healing. PRP also had a significant effect on tendon healing in terms of biomechanical function on the 15th and 30th days, with the best improvement at a PRP dose of 100 µL, especially in the final phase of healing. This study provides detailed biomechanical and histological insights into the tendon healing process, which may be challenging to obtain in human studies due to ethical and logistical constraints. The PRP injection improves healing in the Achilles tendon rupture in Wistar rats.